Sikap Konsistensi Orang Tua dalam Membina Karakter Anak - Aulia Rahmi; Chairullah Chairullah (Serambi Tarbawi, 2023)
Continuity is the main key to consistency, and this consistency is an abstract object that is very liked by Allah SWT. Rasulullah SAW mentioned in one hadith about Allah SWT's love for consistency in doing good deeds. The system of instilling character values is carried out continuously and continuously until habituation appears in the attitudes and behavior of children according to the norms in society. There are three aspects of good character that must be integrated in the process of forming a child's character, namely Knowing the good (moral knowing), Feeling the good (moral feeling), and Acting the good (moral action). The process of forming a child's character which includes several stages must of course be carried out from an early age. This process can only be carried out in the family environment.